2017
DOI: 10.1038/s41598-017-13783-5
|View full text |Cite
|
Sign up to set email alerts
|

Temporal consistency between gross primary production and solar-induced chlorophyll fluorescence in the ten most populous megacity areas over years

Abstract: The gross primary production (GPP) of vegetation in urban areas plays an important role in the study of urban ecology. It is difficult however, to accurately estimate GPP in urban areas, mostly due to the complexity of impervious land surfaces, buildings, vegetation, and management. Recently, we used the Vegetation Photosynthesis Model (VPM), climate data, and satellite images to estimate the GPP of terrestrial ecosystems including urban areas. Here, we report VPM-based GPP (GPPvpm) estimates for the world’s t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 54 publications
(94 reference statements)
4
28
0
Order By: Relevance
“…Many studies have shown that human activities had a negative impact on vegetation cover due to the increase of impervious surfaces but a positive impact on growth length due to the increase of the changing urban environment [18,19,[55][56][57]. All these studies provide basic supports for our study assumption, and our results are also essentially or partly consistent with these conclusions.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Many studies have shown that human activities had a negative impact on vegetation cover due to the increase of impervious surfaces but a positive impact on growth length due to the increase of the changing urban environment [18,19,[55][56][57]. All these studies provide basic supports for our study assumption, and our results are also essentially or partly consistent with these conclusions.…”
Section: Discussionsupporting
confidence: 90%
“…However, this study showed that, compared with PP, the other four land cover types had less EVI and longer LOS than PP, i.e., human activities reduced EVI but extended LOS in the four land cover types affected by human activities. This might be due to the impacts of factors, such as the urban heat island effect and human management on vegetation [19,41,59]. Although the albedo of natural vegetation (PP) was lower and the corresponding RF was larger, the RF in the four land cover types affected by human activities showed a significant increase, and the RF increment was also larger.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, this is the first study that used the VPM method with medium-spatial-resolution satellite imagery to calculate GPP in urban areas; therefore, the results are questionable. Previously, Ciu et al [97] tried to compare GPP-based VPM estimates (using MODIS data) and MODIS GPP data products (MOD17A2) with solar-induced chlorophyll fluorescence (SIF) over the most populous megacity area with better results compared to those produced with the MOD17A2 product. On the other hand, the total annual GPP estimated using the VPM in the current study was not very different from the GPP estimate produced by other LUE models or from the MODIS GPP product, as presented by As-syakur et al [46] in the same location.…”
Section: Annual Changes In Gppmentioning
confidence: 99%
“…Urban ecosystems are increasingly threatened by urban population growth, urban land use expansion(Storkey, Döring et al 2015, Leverkus and Castro 2017, Yang, Guan et al 2018, Kuriqi, Pinheiro et al 2019), and socio-economic activities(Mensah, Veldtman et al 2017, Song and Deng 2017), which affects the value of ecosystem services and ultimately the sustainable development of human society(Costanza, d’Arge et al 1997, Sun, Liu et al 2016). Accurate assessment of ecosystem services value (ESV) is essential for urban construction planning and the improvement and restoration of urban ecosystems(Cui, Xiao et al 2017), so it has received increasing attention from the research community(Costanza, Chichakly et al 2014, Costanza, De Groot et al 2014, Leverkus and Castro 2017, Ossola and Hopton 2017).…”
Section: Introductionmentioning
confidence: 99%